NMR analysis of free and lipid nanodisc anchored CEACAM1 membrane proximal peptides with Ca(2+)/CaM - Ghazarian, Haike (Biochim Biophys Acta Biomembr, 2019)
CEACAM1, a homotypic transmembrane receptor with 12 or 72 amino acid cytosolic domain isoforms, is converted from inactive cis-dimers to active trans-dimers by calcium-calmodulin (Ca(2+)/CaM). Previously, the weak binding of Ca(2+)/CaM to the human 12 AA cytosolic domain was studied using C-terminal anchored peptides. We now show the binding of (15)N labeled Phe-454 cytosolic domain peptides in solution or membrane anchored using NMR demonstrates a significant role for the lipid bilayer. Although binding is increased by the mutation Phe454Ala, this mutation was previously shown to abrogate actin binding. On the other hand, Ca(2+)/CaM binding is abrogated by phosphorylation of nearby Thr-457, a post-translation modification required for actin binding and subsequent in vitro lumen formation. Binding of Ca(2+)/CaM to a membrane proximal peptide from the long 72 AA cytosolic domain anchored to lipid nanodiscs was very weak compared to lipid free conditions, suggesting membrane specific effects between the two isoforms. NMR analysis of (15)N labeled Ca(2+)/CaM with unlabeled peptides showed the C-lobe of Ca(2+)/CaM is involved in peptide interactions, and hydrophobic residues such as Met-109, Val-142 and Met-144 play important roles in binding peptide. This information was incorporated into transmembrane models of CEACAM1 binding to Ca(2+)/CaM. The lack of Ca(2+)/CaM binding to phosphorylated Thr-457, a residue we have previously shown to be phosphorylated by CaMK2D, also dependent on Ca(2+)/CaM, suggests stepwise binding of the cytosolic domain first to Ca(2+)/CaM and then to actin.